International cooperation as regards protection of the environment and fisheries in the Mediterranean Sea - Scovazzi, Tullio (Anuario Español de Derecho Internacional, 2018)
This article discusses the strategic importance of the Mediterranean Sea and the urgent need to protect the marine environment. Concerns about pollution from land-based sources, the high level of urbanization of coastal areas or the intense maritime traffic and the very slow rate of exchange of Mediterranean waters with those of the Atlantic Ocean have prompted a whole set of regional regulations for its special protection. The States bordering the Mediterranean have shown imagination and flexibility in adopting advanced legal instruments. However, much remains to be done on the road to full governance of this regional sea.